Risk-Based Zoning for Urban Flood Mitigation Using HEC-HMS–HEC-RAS 2D Areas - Kurnianingsih, Oktavia; Hadiani, Rr Rintis; Setiawan, Bambang; Sobriyah (Science and Technology Research Centre Universitas PGRI Semarang, 2026)
This study aims to assess the potential for urban inundation and formulate flood mitigation strategies based on spatial analysis. A 2D modelling approach using HEC-HMS and HEC-RAS was applied to simulate the extent and depth of inundation in the urban area of Karanganyar, Indonesia. The models were validated with field observations using RMSE. Model validation confirmed the agreement between simulated and observed data. Validation was quantified using RMSE = 0.42 m across 15 checkpoints, with an average MAE of 0.31 m, and a coefficient of determination (R²) of 0.87. The 2D mesh resolution was set at 10 m, balancing computational efficiency with spatial accuracy. The maximum inundated area reached 3.8 million m² (±0.2 million m²), and the 95th percentile inundation depth was 4.7 m, concentrated in residential and agricultural zones. The results were used to delineate risk zones for prioritised flood mitigation planning. The simulation identified risk zones for prioritised flood mitigation planning, revealing inundated areas of up to 3.8 million m² with maximum depths around 4.7 m (±0.3 m), primarily affecting residential areas, agriculture, and public areas. Risk-based zoning was used to prioritise mitigation strategies, including improved drainage and the construction of infiltration ponds. The risk-based zoning approach demonstrated that implementing infiltration ponds and improved drainage in Priority Zone A could reduce flood exposure by approximately 28% under a simulated 20-year return period storm. These findings provide a measurable basis for adaptive flood mitigation strategies in urban areas.